Hollow dahlia-shaped nickel-cobalt selenide composite electro-catalytic material as well as synthesis method and application of hollow dahlia-shaped nickel-cobalt selenide composite electro-catalytic material
The hollow dahlia-shaped nickel-cobalt selenide composite electrocatalytic material was prepared by hydrothermal-solvent thermal binding method, which solved the problem of electron transport obstacles caused by the low spin state of the nickel-based material under alkaline conditions, and achieved efficient and stable electrocatalytic reactions.
Patent Information
- Application Number
- CN202411774101.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing nickel-based electrocatalytic materials exhibit low spin state under alkaline conditions, resulting in hindered electron transport and affecting the efficiency of electrocatalytic reactions.
Hollow dahlia-shaped nickel-cobalt selenide composite electrocatalytic material was prepared by hydrothermal-solvent thermal bonding. The crystal growth and microstructure were controlled by SiO2 spheres as templates to form a NiSe/Co9Se8 composite material with a high specific surface area and a porous structure.
It achieves high activity, high stability and excellent electrocatalytic HER and OER performance under alkaline conditions, and improves the electrocatalytic reaction efficiency.
Smart Images

Figure CN119615250A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrocatalytic materials, and in particular relates to a hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material, a synthesis method thereof, and an application thereof. Background Art
[0002] In today's world, energy and environmental challenges are becoming increasingly severe. Against this backdrop, the hydrogen economy has attracted significant attention as a clean and efficient energy solution. Electrocatalytic water splitting technology can produce "green hydrogen" from renewable energy sources such as wind, hydro, and solar power. With its advantages of readily available raw materials, high energy efficiency, simple operation, and environmental friendliness, it is currently one of the most promising sustainable hydrogen production methods.
[0003] The electrocatalytic water splitting process mainly involves two half-reactions: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) (Lakhan, M.; Hanan, A.; Hussain, A.; Soomro, I.; Wang, Y.; Ahmed, M.; Aftab, U.; Sun, H.; Arandiyan, H. Transition metal-based electrocatalysts for alkaline overall water splitting: advancements, challenges, and perspectives, Chemical Communications, 2024, 60(39): 5104-5135.). Among them, HER is the process of reducing protons to hydrogen at the cathode, and its efficiency and selectivity have a crucial impact on the economy and practicality of the entire water splitting hydrogen production. OER, on the other hand, occurs at the anode and is a complex process involving multiple electron transfer steps. Its kinetics are relatively slow, and it often becomes the rate-limiting step of the water splitting reaction. Therefore, it is of great significance to develop efficient and stable bifunctional electrocatalysts.
[0004] Transition metal chalcogenides have the advantages of adjustable phase structure, high carrier mobility and flexible electronic structure, which can effectively improve the efficiency of electrocatalytic reactions and have great application potential in the field of energy conversion. Compared with oxygen and sulfur in the same main group, selenium has a large radius, strong metallicity and low electronegativity, which makes selenides often have easier to modulate electronic structures and bonding states, thereby improving the efficiency of electrocatalytic reactions (Chen, D.; Zhao, Z.; Chen, G.; Li, T.; Chen, J.; Ye, Z.; Lu, J. Metal selenides for energy storage and conversion: A comprehensive review. Coordination Chemistry Reviews, 2023, 479: 214984.). Among them, nickel-based electrocatalytic materials are low in price, highly conductive and have good stability under alkaline conditions, making them suitable for large-scale applications. Therefore, nickel selenide has attracted widespread attention due to its advantages such as simple synthesis method, high conductivity and rich crystal phase. However, nickel-based materials often exhibit a low-spin state, that is, their low-energy orbitals (t 2g ) is fully filled, which will lead to hindered electron transport in pure nickel-based materials (Xu, J.; Ruan, J.; Jian, Y.; Lao, J.; Li, Z.; Xie, F.; Jin, Y.; Yu, X.; Lee, M.; Wang, Z.; Wang, N.; Meng, H. Cobalt-doping induced formation of five-coordinated nickel selenide for enhanced ethanol assisted overall watersplitting, Small, 2024, 20(11): 2305905.). Summary of the Invention
[0005] The purpose of the present invention is to provide a hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material, its synthesis method and application, which can precisely control crystal growth and microstructure, thereby preparing an electrocatalyst with high activity, high stability and high specific surface area, and the product exhibits excellent electrocatalytic HER and OER performance under alkaline conditions.
[0006] To achieve the above object, the synthesis method adopted in the present invention comprises the following steps:
[0007] S1: Disperse 285.24-356.55 mg of nickel source powder in 25-30 mL of deionized water and mix well. Then, add 133.75-149.8 mg of ammonium chloride and 280.36-308.4 mg of hexamethylenetetramine powder and stir well. Finally, add alkaline solution and stir well. Adjust the pH value to 8.5-9.0 to obtain solution A.
[0008] S2: Ultrasonic dispersion of 210.35-228.38 mg of SiO2 powder in 25-30 mL of deionized water, stirring to obtain solution B;
[0009] S3: adding solution A dropwise to solution B, stirring evenly, and then pouring into a polytetrafluoroethylene hydrothermal reactor, heating to 125-135° C. and maintaining for 25-30 hours, and then naturally cooling to room temperature, and then removing ultrapure water and ethanol from the reaction product obtained in the polytetrafluoroethylene hydrothermal reactor, centrifuging, and vacuum drying to obtain nickel silicon hydroxide precursor powder;
[0010] S4: Dissolve 78.96-102.65 mg of Se powder in 2.2-2.5 mL of hydrazine hydrate and stir to obtain solution C;
[0011] S5: adding solution C to a mixed solution of 9-11 mL of ethylene glycol and 12-14 mL of ethylenediamine and stirring until uniform, thereby obtaining solution D;
[0012] S6: Add 237.9-285.5 mg of a cobalt source, 88.91-114.14 mg of polyvinyl pyrrolidone, and 150-155 mg of nickel silicon hydroxide precursor powder to solution D, and stir evenly to obtain solution E;
[0013] S7: Solution E is added to a hydrothermal reactor of para-polyphenylene, heated to 175-180°C and maintained for 15-18 hours, and then naturally cooled to room temperature. The reaction product obtained in the hydrothermal reactor of para-polyphenylene is then centrifuged with ultrapure water and ethanol and vacuum dried to obtain the target product NiSe / Co9Se8.
[0014] Preferably, the nickel source in step S1 is one or more of nickel chloride hexahydrate, nickel nitrate hexahydrate or nickel acetylacetonate, and the alkaline solution is one or more of 1 mol / L ammonia water, sodium hydroxide or potassium hydroxide.
[0015] Preferably, the stirring process in step S1, step S5 and step S6 is magnetic stirring.
[0016] Preferably, the filling ratio of the mixed solution of A and B to the hydrothermal reactor in step S3 is 54% to 65%.
[0017] Preferably, the reaction products in step S3 and step S7 are subjected to alternating centrifugation treatment with ultrapure water and anhydrous ethanol for 3 to 4 times, and the vacuum drying temperature is 70 to 80°C.
[0018] Preferably, the stirring method in step S4 is magnetic stirring at a temperature of 62-65°C.
[0019] Preferably, the cobalt source in step S6 is one or more of cobalt chloride hexahydrate, cobalt nitrate hexahydrate or cobalt acetylacetonate.
[0020] Preferably, the filling ratio of the solution E to the hydrothermal reactor of para-polyphenylene in step S7 is 46-55%.
[0021] A hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material prepared by the method described in any one of the above items.
[0022] An application of the hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material in electrocatalytic hydrogen and oxygen evolution reactions under alkaline conditions.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) In terms of preparation strategy, this scheme adopts a hydrothermal-solvothermal method to prepare hollow dahlia-shaped nickel cobalt selenide composite electrocatalytic materials, which has significant advantages. Specifically, a nickel silicon hydroxide precursor is first prepared by a hydrothermal reaction method. This method is simple to operate, environmentally friendly and energy-saving, and the morphology and structure are easy to control. Then, a solvothermal method is used to prepare NiSe / Co9Se8 hollow nanoflower composite materials. This method can effectively inhibit oxidation and has the advantages of a wide range of applications, easy control of the reaction process, and a low crystallization temperature. Therefore, the combination of the two methods can accurately control crystal growth and microstructure, thereby preparing an electrocatalyst with high activity, high stability and high specific surface area;
[0025] (2) In this scheme, SiO2 spheres are used as templates, which have rich porous structures and high specific surface areas. Therefore, the electrocatalyst synthesized using it as a precursor is more regular in structure, which is conducive to the uniform distribution of active sites. In addition, its high chemical stability enables it to maintain its structural integrity during the synthesis of the electrocatalyst. It is also easy to perform surface modification through various chemical methods to precisely control the composition and structure of the electrocatalyst, thereby improving the electrocatalytic performance.
[0026] (3) The NiSe / Co9Se8 hollow nanoflower structure prepared in this scheme not only has a larger specific surface area and more accessible active sites, which can effectively increase the full contact between the electrolyte and the catalyst and enhance the catalytic activity, but also its unique hollow and porous structure can serve as a fast mass transfer channel, accelerating the transmission of ions and electrons, further improving the electrocatalytic performance;
[0027] (4) This scheme also introduces a morphology control agent hexamethylenetetramine. By strictly controlling the mass ratio of hexamethylenetetramine to nickel source and ammonium chloride, reaction temperature, reaction time, and reaction filling ratio, the induction effect of hexamethylenetetramine is fully utilized to achieve the control of the structure of the nickel silicon hydroxide precursor prepared using SiO2 balls as templates during the reaction process.
[0028] (5) In this scheme, polyvinyl pyrrolidone, a morphology control agent, is added to the reaction solvent. By strictly coordinating the volume of ethylene glycol and ethylenediamine, the concentration and ratio of the cobalt source and selenium source, the reaction time, the reaction temperature, and the reaction filling ratio, the state of the NiSe / Co9Se8 hollow nanoflower composite material in the reaction is controlled;
[0029] (6) In this scheme, ethylene glycol and ethylenediamine are used as solvents for the dissolution heat reaction. The mixed solvent synthesis electrocatalyst utilizes the reducibility and good dispersibility of ethylene glycol and the coordination ability of ethylenediamine to effectively control the particle size and morphology of the catalyst, thereby improving the activity and stability of the catalyst.
[0030] (7) This scheme uses SiO2 balls as templates to construct NiSe / Co9Se8 hollow nanoflower composite materials, and utilizes the advantages of multi-component synergistic effects and structural complementarity to improve the electrocatalytic performance of the material. Among them, by introducing cobalt selenide materials with special valence electron structures and adjustable binding energy with oxygen-containing groups, the electron distribution of active sites can be changed to optimize the adsorption energy / desorption energy of reaction intermediates, thereby improving the electrocatalytic performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The X-ray diffraction (XRD) pattern of the NiSe / Co9Se8 composite electrocatalyst prepared in Example 1 of the present invention;
[0032] Figure 2 This is a low-magnification scanning electron microscope (SEM) photograph of the NiSe / Co9Se8 composite electrocatalyst prepared in Example 1 of the present invention;
[0033] Figure 3 This is a high-magnification scanning electron microscope (SEM) photograph of the NiSe / Co9Se8 composite electrocatalyst prepared in Example 1 of the present invention;
[0034] Figure 4This is a graph showing the hydrogen evolution performance (HER) of the NiSe / Co9Se8 composite electrocatalyst prepared in Example 1 of the present invention under alkaline conditions, showing a linear sweep voltammetry (LSV) curve;
[0035] Figure 5 This is the oxygen evolution performance diagram (OER) of the NiSe / Co9Se8 composite electrocatalyst prepared in Example 1 of the present invention under alkaline conditions, showing the linear sweep voltammetry (LSV) curve. DETAILED DESCRIPTION
[0036] The present invention will be further described in detail below with reference to specific embodiments, which are intended to explain the present invention rather than to limit it.
[0037] Example 1:
[0038] S1: Disperse 285.24 mg of nickel chloride hexahydrate in 25 mL of deionized water and mix well. Then, add 133.75 mg of ammonium chloride and 280.36 mg of hexamethylenetetramine powder. Stir magnetically until uniform. Then, add 1 mol / L ammonia water, stir until uniform, and adjust the pH to 9.0 to obtain solution A.
[0039] S2: Disperse 210.35 mg of SiO2 powder in 25 mL of deionized water and ultrasonicate for 1.2 h. Stir until uniform to obtain solution B.
[0040] S3: Solution A was added dropwise to solution B, stirred for 30 minutes, and then poured into a polytetrafluoroethylene hydrothermal reactor at a filling ratio of 54%. The polytetrafluoroethylene hydrothermal reactor was heated to 125°C and maintained for 30 hours, and then naturally cooled to room temperature. The reaction product obtained in the polytetrafluoroethylene hydrothermal reactor was then alternately centrifuged three times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 70°C for 18 hours to obtain nickel silicon hydroxide precursor powder;
[0041] S4: Dissolve 78.96 mg of Se powder in 2.2 mL of hydrazine hydrate and stir magnetically at 62 °C for 50 min to obtain solution C.
[0042] S5: Solution C was added to a mixed solution of 9 mL of ethylene glycol and 12 mL of ethylenediamine and magnetically stirred for 25 min to obtain solution D.
[0043] S6: 237.9 mg of cobalt chloride hexahydrate, 88.91 mg of polyvinyl pyrrolidone, and 150 mg of nickel silicon hydroxide precursor powder were added to solution D, and the mixture was magnetically stirred to obtain solution E. The stirring time was 25 min.
[0044] S7: Solution E is added to the hydrothermal reactor of para-polyphenylene at a filling ratio of 46%, and the para-polyphenylene hydrothermal reactor is heated to 175°C and maintained for 18 hours, and then naturally cooled to room temperature. The reaction product obtained in the para-polyphenylene hydrothermal reactor is then alternately centrifuged three times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 70°C for 15 hours to obtain the NiSe / Co9Se8 target product.
[0045] Figure 1 This is the X-ray diffraction (XRD) pattern of the NiSe / Co9Se8 composite electrocatalyst prepared in Example 1 of the present invention. It can be seen from the figure that there are two phases, one is the diffraction peak of NiSe (PDF#75-0610), and the other is the diffraction peak of Co9Se8 (PDF#09-0233).
[0046] Figure 2 This is a low-magnification scanning electron microscope (SEM) photograph of the NiSe / Co9Se8 composite electrocatalyst prepared in Example 1 of the present invention, showing the nanoflower morphology of nanosheet assembly.
[0047] Figure 3 This is a high-magnification scanning electron microscope (SEM) photograph of the NiSe / Co9Se8 composite electrocatalyst prepared in Example 1 of the present invention. It can be observed that the morphology of NiSe / Co9Se8 is a hollow nanoflower structure.
[0048] Figure 4 The linear sweep voltammetry (LSV) curve of the NiSe / Co9Se8 composite electrocatalyst prepared in Example 1 of the present invention shows the hydrogen production performance (HER) under alkaline conditions. The NiSe / Co9Se8 composite material exhibits good electrocatalytic hydrogen production activity with a current density of 10 mA / cm 2 The required overpotential is 152 mV respectively.
[0049] Figure 5 The linear sweep voltammetry (LSV) curve of the NiSe / Co9Se8 composite electrocatalyst prepared in Example 1 of the present invention shows the oxygen evolution performance (OER) under alkaline conditions. The NiSe / Co9Se8 composite material exhibits good electrocatalytic oxygen evolution activity with a current density of 10 mA / cm 2 The required overpotential is 280 mV respectively.
[0050] Example 2:
[0051] S1: Disperse 300 mg of nickel nitrate hexahydrate powder in 26 mL of deionized water and mix well. Then, add 140 mg of ammonium chloride and 290 mg of hexamethylenetetramine powder. Stir magnetically until evenly mixed. Then, add 1 mol / L sodium hydroxide solution, stir evenly, and adjust the pH to 8.5 to obtain solution A.
[0052] S2: Disperse 215 mg of SiO2 powder in 26 mL of deionized water and ultrasonicate for 1.3 h. Stir thoroughly to obtain solution B.
[0053] S3: Solution A was added dropwise to solution B, stirred for 32 minutes, and then poured into a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 56%. The polytetrafluoroethylene hydrothermal reactor was heated to 127°C and maintained for 29 hours, and then naturally cooled to room temperature. The reaction product obtained in the polytetrafluoroethylene hydrothermal reactor was then alternately centrifuged three times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 72°C for 17.5 hours to obtain nickel silicon hydroxide precursor powder;
[0054] S4: 85 mg of Se powder was dissolved in 2.3 mL of hydrazine hydrate and magnetically stirred at 63 °C for 52 min to obtain solution C.
[0055] S5: Solution C was added to a mixed solution of 10 mL of ethylene glycol and 13 mL of ethylenediamine and magnetically stirred for 26 min to obtain solution D.
[0056] S6: 250 mg of cobalt nitrate hexahydrate, 95 mg of polyvinyl pyrrolidone, and 152 mg of nickel silicon hydroxide precursor powder were added to solution D, and the mixture was stirred magnetically for 26 min to obtain solution E.
[0057] S7: Solution E is added to the hydrothermal reactor of para-polyphenylene at a filling ratio of 50%, and the para-polyphenylene hydrothermal reactor is heated to 176°C and maintained for 17 hours, and then naturally cooled to room temperature. The reaction product obtained in the para-polyphenylene hydrothermal reactor is then alternately centrifuged three times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 72°C for 15 hours to obtain the NiSe / Co9Se8 target product.
[0058] Example 3:
[0059] S1: Disperse 320 mg of nickel acetylacetonate in 27 mL of deionized water and mix well. Then, add 145 mg of ammonium chloride and 300 mg of hexamethylenetetramine powder. Stir magnetically until evenly mixed. Then, add 1 mol / L potassium hydroxide solution, stir evenly, and adjust the pH to 8.8 to obtain solution A.
[0060] S2: Disperse 220 mg of SiO2 powder in 27 mL of deionized water and ultrasonicate for 1.4 h. Stir until uniform to obtain solution B.
[0061] S3: Solution A was added dropwise to solution B, stirred for 34 minutes, and then poured into a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 58.5%. The polytetrafluoroethylene hydrothermal reactor was heated to 129°C and maintained for 28 hours, and then naturally cooled to room temperature. The reaction product obtained in the polytetrafluoroethylene hydrothermal reactor was then alternately centrifuged three times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 74°C for 17 hours to obtain nickel silicon hydroxide precursor powder;
[0062] S4: 92 mg of Se powder was dissolved in 2.4 mL of hydrazine hydrate and magnetically stirred at 64 °C for 53 min to obtain solution C.
[0063] S5: Solution C was added to a mixed solution of 10.5 mL of ethylene glycol and 13.5 mL of ethylenediamine and magnetically stirred for 27 min to obtain solution D.
[0064] S6: 265 mg of cobalt acetylacetonate, 102 mg of polyvinyl pyrrolidone, and 153 mg of nickel silicon hydroxide precursor powder were added to solution D, and the mixture was magnetically stirred to obtain solution E. The stirring time was 27 min.
[0065] S7: Solution E was added to the hydrothermal reactor of para-polyphenylene at a filling ratio of 52.8%, and the para-polyphenylene hydrothermal reactor was heated to 177°C and maintained for 16.5 hours, and then naturally cooled to room temperature. The reaction product obtained in the para-polyphenylene hydrothermal reactor was then alternately centrifuged four times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 74°C for 14 hours to obtain the NiSe / Co9Se8 target product.
[0066] Example 4:
[0067] S1: 330 mg of nickel chloride hexahydrate and nickel nitrate hexahydrate powder were dispersed in 28 mL of deionized water at a mass ratio of 1:1 and mixed evenly. 148 mg of ammonium chloride and 305 mg of hexamethylenetetramine powder were added and magnetically stirred until evenly mixed. 1 mol / L ammonia water and sodium hydroxide solution were added and stirred until evenly mixed. The pH value was adjusted to 9.0 to obtain solution A.
[0068] S2: Disperse 225 mg of SiO2 powder in 28 mL of deionized water and ultrasonicate for 1.45 h. Stir thoroughly to obtain solution B.
[0069] S3: Solution A was added dropwise to solution B, stirred for 36 minutes, and then poured into a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 60%. The polytetrafluoroethylene hydrothermal reactor was heated to 131°C and maintained for 27 hours, and then naturally cooled to room temperature. The reaction product obtained in the polytetrafluoroethylene hydrothermal reactor was then alternately centrifuged with ultrapure water and ethanol for 4 times, and dried under vacuum conditions at a vacuum drying temperature of 76°C for 16.5 hours to obtain nickel silicon hydroxide precursor powder;
[0070] S4: Dissolve 98 mg of Se powder in 2.45 mL of hydrazine hydrate and stir magnetically at 64.5 °C for 54 min to obtain solution C.
[0071] S5: Solution C was added to a mixed solution of 10.8 mL of ethylene glycol and 13.8 mL of ethylenediamine and magnetically stirred for 28 min to obtain solution D.
[0072] S6: 275 mg of cobalt chloride hexahydrate and cobalt nitrate hexahydrate in a mass ratio of 1:1, 108 mg of polyvinyl pyrrolidone, and 154 mg of nickel silicon hydroxide precursor powder were added to solution D, and the mixture was magnetically stirred to obtain solution E. The stirring time was 28 min.
[0073] S7: Solution E was added to the hydrothermal reactor of para-polyphenylene at a filling ratio of 54%, and the para-polyphenylene hydrothermal reactor was heated to 178°C and maintained for 16 hours, and then naturally cooled to room temperature. The reaction product obtained in the para-polyphenylene hydrothermal reactor was then alternately centrifuged four times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 76°C for 14 hours to obtain the NiSe / Co9Se8 target product.
[0074] Example 5:
[0075] S1: Disperse 345 mg of nickel chloride hexahydrate and nickel acetylacetonate powder in a mass ratio of 1:1 in 29 mL of deionized water and mix thoroughly. Then, add 149 mg of ammonium chloride and 307 mg of hexamethylenetetramine powder. Stir thoroughly with a magnetic stirrer. Then, add 1 mol / L ammonia water and potassium hydroxide solution, stir thoroughly, and adjust the pH to 8.5 to obtain solution A.
[0076] S2: Disperse 227 mg of SiO2 powder in 29 mL of deionized water and ultrasonicate for 1.48 h. Stir thoroughly to obtain solution B.
[0077] S3: Solution A was added dropwise to solution B, stirred for 38 minutes, and then poured into a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 62.5%. The polytetrafluoroethylene hydrothermal reactor was heated to 133°C and maintained for 26 hours, and then naturally cooled to room temperature. The reaction product obtained in the polytetrafluoroethylene hydrothermal reactor was then alternately centrifuged with ultrapure water and ethanol for 4 times, and dried under vacuum conditions at a vacuum drying temperature of 78°C for 16 hours to obtain nickel silicon hydroxide precursor powder;
[0078] S4: Dissolve 98 mg of Se powder in 2.48 mL of hydrazine hydrate and stir magnetically at 64.8 °C for 54.5 min to obtain solution C.
[0079] S5: Solution C was added to a mixed solution of 10.9 mL of ethylene glycol and 13.9 mL of ethylenediamine and magnetically stirred for 29 min to obtain solution D.
[0080] S6: 280 mg of cobalt chloride hexahydrate and cobalt acetylacetonate in a mass ratio of 1:1, 112 mg of polyvinyl pyrrolidone, and 154.5 mg of nickel silicon hydroxide precursor powder were added to solution D, and the mixture was magnetically stirred to obtain solution E. The stirring time was 29 min.
[0081] S7: Solution E was added to the hydrothermal reactor of para-polyphenylene at a filling ratio of 54.5%, and the para-polyphenylene hydrothermal reactor was heated to 179°C and maintained for 15.5 hours, and then naturally cooled to room temperature. The reaction product obtained in the para-polyphenylene hydrothermal reactor was then alternately centrifuged four times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 78°C for 13 hours to obtain the NiSe / Co9Se8 target product.
[0082] Example 6:
[0083] S1: Disperse 356.55 mg of nickel nitrate hexahydrate and nickel acetylacetonate powder in a mass ratio of 1:1 in 30 mL of deionized water and mix evenly. Then, add 149.8 mg of ammonium chloride and 308.4 mg of hexamethylenetetramine powder. Stir magnetically until evenly mixed. Then, add 1 mol / L potassium hydroxide and sodium hydroxide solutions, stir evenly, and adjust the pH to 8.5 to obtain solution A.
[0084] S2: Disperse 228.38 mg of SiO2 powder in 30 mL of deionized water and ultrasonicate for 1.5 h. Stir until uniform to obtain solution B.
[0085] S3: Solution A was added dropwise to solution B, stirred for 40 minutes, and then poured into a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 65%. The polytetrafluoroethylene hydrothermal reactor was heated to 135°C and maintained for 25 hours, and then naturally cooled to room temperature. The reaction product obtained in the polytetrafluoroethylene hydrothermal reactor was then alternately centrifuged with ultrapure water and ethanol for 4 times, and dried under vacuum conditions at a vacuum drying temperature of 80°C for 15 hours to obtain nickel silicon hydroxide precursor powder;
[0086] S4: Dissolve 102.65 mg of Se powder in 2.5 mL of hydrazine hydrate and stir magnetically at 65 °C for 55 min to obtain solution C.
[0087] S5: Solution C was added to a mixed solution of 11 mL of ethylene glycol and 14 mL of ethylenediamine and magnetically stirred for 30 min to obtain solution D.
[0088] S6: 285.5 mg of cobalt nitrate hexahydrate and cobalt acetylacetonate in a mass ratio of 1:1, 114.14 mg of polyvinyl pyrrolidone, and 155 mg of nickel silicon hydroxide precursor powder were added to solution D, and the mixture was magnetically stirred to obtain solution E. The stirring time was 30 min.
[0089] S7: Solution E is added to the hydrothermal reactor of para-polyphenylene at a filling ratio of 55%, and the para-polyphenylene hydrothermal reactor is heated to 180°C and maintained for 15 hours, and then naturally cooled to room temperature. The reaction product obtained in the para-polyphenylene hydrothermal reactor is then alternately centrifuged four times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 80°C for 13 hours to obtain the NiSe / Co9Se8 target product.
[0090] Example 7:
[0091] S1: 356.55 mg of nickel nitrate hexahydrate and nickel acetylacetonate powder were dispersed in 30 mL of deionized water at any mass ratio and mixed evenly. 149.8 mg of ammonium chloride and 308.4 mg of hexamethylenetetramine powder were added and stirred evenly by magnetic stirring. 1 mol / L potassium hydroxide and sodium hydroxide solutions were added and stirred evenly. The pH value was adjusted to 9.0 to obtain solution A.
[0092] S2: Disperse 228.38 mg of SiO2 powder in 30 mL of deionized water and ultrasonicate for 1.5 h. Stir until uniform to obtain solution B.
[0093] S3: adding solution A dropwise to solution B, stirring evenly, and then pouring the mixture into a polytetrafluoroethylene hydrothermal reactor with a filling ratio of 62%, heating the polytetrafluoroethylene hydrothermal reactor to 135°C and maintaining it for 25 hours, and then naturally cooling it to room temperature. The reaction product obtained in the polytetrafluoroethylene hydrothermal reactor is then subjected to alternating centrifugation treatment four times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 80°C for 15 hours to obtain nickel silicon hydroxide precursor powder;
[0094] S4: Dissolve 102.65 mg of Se powder in 2.5 mL of hydrazine hydrate and stir magnetically at 65 °C for 55 min to obtain solution C.
[0095] S5: Solution C was added to a mixed solution of 11 mL of ethylene glycol and 14 mL of ethylenediamine and magnetically stirred for 30 min to obtain solution D.
[0096] S6: 285.5 mg of cobalt nitrate hexahydrate and cobalt chloride hexahydrate in any mass ratio, 114.14 mg of polyvinyl pyrrolidone, and 155 mg of nickel silicon hydroxide precursor powder were added to solution D, and the mixture was stirred magnetically to obtain solution E. The stirring time was 30 min.
[0097] S7: Solution E is added to the hydrothermal reactor of para-polyphenylene at a filling ratio of 53%, and the para-polyphenylene hydrothermal reactor is heated to 180°C and maintained for 15 hours, and then naturally cooled to room temperature. The reaction product obtained in the para-polyphenylene hydrothermal reactor is then alternately centrifuged four times with ultrapure water and ethanol, and dried under vacuum conditions at a vacuum drying temperature of 80°C for 13 hours to obtain the NiSe / Co9Se8 target product.
[0098] The above content is a further detailed description of the present invention in combination with specific embodiments, and it cannot be considered that the specific implementation of the present invention is limited to these inventions. For ordinary technicians in the technical field of the present invention, without departing from the concept of the present invention, they can also make several simple deductions or substitutions, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. A method for synthesizing a hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material, characterized in that: The following steps are involved: S1: 285.24-356.55 mg of nickel source powder is dispersed in 25-30 mL of deionized water and mixed evenly, then 133.75-149.8 mg of ammonium chloride and 280.36-308.4 mg of hexamethylenetetramine powder are added and stirred evenly, and finally an alkaline solution is added and stirred evenly, and the pH value is adjusted to 8.5-9.0 to obtain solution A; S2: Ultrasonic dispersion of 210.35-228.38 mg of SiO2 powder in 25-30 mL of deionized water, stirring evenly to obtain solution B; S3: adding solution A dropwise into solution B, stirring evenly, pouring into a polytetrafluoroethylene hydrothermal reactor, heating to 125-135° C. and maintaining for 25-30 hours, then naturally cooling to room temperature, and then centrifuging and vacuum drying the reaction product obtained in the polytetrafluoroethylene hydrothermal reactor with ultrapure water and ethanol to obtain nickel silicon hydroxide precursor powder; S4: Dissolve 78.96-102.65 mg of Se powder in 2.2-2.5 mL of hydrazine hydrate and stir to obtain solution C; S5: adding solution C to a mixed solution of 9-11 mL of ethylene glycol and 12-14 mL of ethylenediamine and stirring the mixture to obtain solution D; S6: Add 237.9-285.5 mg of cobalt source, 88.91-114.14 mg of polyvinyl pyrrolidone and 150-155 mg of nickel silicon hydroxide precursor powder to solution D, and stir evenly to obtain solution E; S7: Add solution E into the hydrothermal reactor of para-polyphenylene, heat to 175-180°C and maintain for 15-18 hours, then naturally cool to room temperature. Then, the reaction product obtained in the hydrothermal reactor of para-polyphenylene is treated with ultrapure water and ethanol by centrifugation and vacuum drying to obtain the target product NiSe / Co9Se8.
2. The method for synthesizing a hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material according to claim 1, characterized in that: The nickel source in step S1 is one or more of nickel chloride hexahydrate, nickel nitrate hexahydrate or nickel acetylacetonate, and the alkaline solution is one or more of 1 mol / L ammonia water, sodium hydroxide or potassium hydroxide.
3. The method for synthesizing a hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material according to claim 1, characterized in that: The stirring in step S1, step S5 and step S6 is magnetic stirring.
4. The method for synthesizing a hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material according to claim 1, characterized in that: The filling ratio of the mixed solution of A and B to the hydrothermal reaction kettle in step S3 is 54% to 65%.
5. The method for synthesizing a hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material according to claim 1, characterized in that: The reaction products in step S3 and step S7 are subjected to alternating centrifugation treatment with ultrapure water and anhydrous ethanol for 3 to 4 times, and the vacuum drying temperature is 70 to 80°C.
6. The method for synthesizing a hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material according to claim 1, characterized in that: The stirring method in step S4 is specifically magnetic stirring at a temperature of 62-65°C.
7. The method for synthesizing a hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material according to claim 1, characterized in that: The cobalt source in step S6 is one or more of cobalt chloride hexahydrate, cobalt nitrate hexahydrate or cobalt acetylacetonate.
8. The method for synthesizing a hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material according to claim 1, characterized in that: The filling ratio of the solution E to the hydrothermal reaction kettle of para-polyphenylene in step S7 is 46-55%.
9. A hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material prepared by the method according to any one of claims 1 to 8.
10. Use of the hollow dahlia-shaped nickel-cobalt-selenide composite electrocatalytic material as claimed in claim 9 in electrocatalytic hydrogen evolution and oxygen evolution reactions under alkaline conditions.
Citation Information
Patent Citations
Co-Se compound nanotube@ foam Ni composite array material as well as preparation method and application thereof
CN108993545A
APPARATUS AND METHOD FOR TRAINING NeRF MODEL
KR102793927B1